Effects of two dietary probiotics (Bacillus subtilis or licheniformis) with two prebiotics (mannan or fructo oligosaccharide) in Japanese eel, Anguilla japonica. (28th October 2019) - Park, Youngjin; Kim, Haham; Won, Seonghun; Hamidoghli, Ali; Hasan, Md Tawheed; Kong, In‐Soo; Bai, Sungchul C.
Abstract: A 12‐week feeding trial was conducted to investigate the effects of two dietary probiotics; Bacillus subtilis KCTC 2217 or Bacillus licheniformis KCCM 11775 with two prebiotics; mannan oligosaccharide (MOS) or fructooligosaccharide (FOS) in Japanese eel. Fish averaging 12.8 ± 0.47 g (mean ± SD ) were randomly distributed into five treatments with triplicate tanks. A basal control diet (CON) and four synbiotic diets supplementing B. subtilis + MOS (BSM), B. subtilis + FOS (BSF), B. licheniformis + MOS (BLM), and B. licheniformis + FOS (BLF). Weight gain and specific growth rate of fish fed all synbiotic diets were higher than those of fish fed CON. Immune‐related gene expression of heat shock protein 70 and immunoglobulin M of fish fed BSF and BLM were significantly higher than those of fish fed CON. Fish fed BSF and BLM had significantly higher intestinal villi length than those of fish fed BLF and CON ( p < .05). Disease resistance against Aeromonas hydrophila of fish fed all synbiotic diets were significantly higher than those of fish fed CON ( p < .05). Therefore, these results indicated that dietary B. subtilis with FOS (BSF) and B. licheniformis with MOS (BLM) could have beneficial effects on intestinal morphology, and immune‐related gene expression in Japanese eel.